2022
DOI: 10.1038/s41467-022-31436-8
|View full text |Cite
|
Sign up to set email alerts
|

The 22q11.2 region regulates presynaptic gene-products linked to schizophrenia

Abstract: It is unclear how the 22q11.2 deletion predisposes to psychiatric disease. To study this, we generated induced pluripotent stem cells from deletion carriers and controls and utilized CRISPR/Cas9 to introduce the heterozygous deletion into a control cell line. Here, we show that upon differentiation into neural progenitor cells, the deletion acted in trans to alter the abundance of transcripts associated with risk for neurodevelopmental disorders including autism. In excitatory neurons, altered transcripts enco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 113 publications
1
14
0
Order By: Relevance
“…Recent technological advances have enabled the reproduction of pathological conditions in vitro by creating patient-derived or mutation-carrying induced pluripotent stem (iPS) cells and then differentiating them into central nervous system cells or miniature brains. Studies of etiologically valid cellular models of schizophrenia produced with this technology, including those with 22q11.2 deletion, 16p11.2 deletion/duplication, SETD1A LOF/PTV, and NRXN LOF/PTV, have been conducted and reported [94][95][96][97][98][99][100][101][102][103][104][105][106] (Table 3).…”
Section: Cellular Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent technological advances have enabled the reproduction of pathological conditions in vitro by creating patient-derived or mutation-carrying induced pluripotent stem (iPS) cells and then differentiating them into central nervous system cells or miniature brains. Studies of etiologically valid cellular models of schizophrenia produced with this technology, including those with 22q11.2 deletion, 16p11.2 deletion/duplication, SETD1A LOF/PTV, and NRXN LOF/PTV, have been conducted and reported [94][95][96][97][98][99][100][101][102][103][104][105][106] (Table 3).…”
Section: Cellular Modelsmentioning
confidence: 99%
“…Also, morphological alteration of soma and dendrite were common except for iPS cell-derived neurons with NRXN1 deletion [94,98,101,102,106]. Abnormal neural activities are identified in multiple patient-derived or genetically engineered iPS cellderived neurons, however, the directions of the abnormalities are sometimes inconsistent across models manipulating different genes [97,[101][102][103][104][105][106]. Though it may be due to artifacts depending on the differences in the experimental designs, another possibility is that imbalanced excitatory/inhibitory activities themselves [107], regardless of the direction of abnormality, are important in schizophrenia pathology.…”
Section: Cellular Modelsmentioning
confidence: 99%
“…To study molecular pathways in glia-neuron interactions, we first assembled a sample set of 32 karyotypically normal hPSC lines (29 iPSC and three ESC lines) derived from neurotypical donors 15,18 Figure 1, Table S1 ). These lines were differentiated into excitatory neurons using a well-characterized protocol that combines Ngn2 expression with forebrain patterning factors to robustly generate a homogenous population of excitatory neurons (N= 32 cell lines) 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Although 22q11.2DS is a contiguous gene syndrome, the size of the deletion does not influence the severity of the phenotypic manifestations: LCR A–D deletions most often present similar phenotype and severity compared to smaller proximal deletion (LCR A–B) [ 53 , 54 ]. However, it was observed that central (LCR B–D) and distal deletions (LCR D–E/F) usually have a milder phenotype [ 55 ], a fact also observed in our study; at the same time, the incomplete penetrance and variable expressivity can also be noticed, especially in inherited deletions, where the same size and type of deletion can determine a severe phenotype but also a discrete or even asymptomatic one.…”
Section: Discussionmentioning
confidence: 99%